Anchor, float or abandon ship: Exchange rate regimes for the acceccion countries - Willem Buiter; Clemens Grafe (EIB Papers, 2002)
This paper investigates the appropriate exchange rate regimes, both prior to and following European Union accession, for those former centrally planned Central and Eastern European countries that are currently candidates for full membership in the European Union (1). The exchange rate regime is a key determinant of a countrys macroeconomic stability, which is in turn a key determinant of the investment climate. The choice of exchange rate regime is therefore of great relevance to all who are interested in the transition process. It now seems likely that as many as eight out of the ten candidate countries from the EBRDs region of operations will become EU members by early 2004, in time to participate in the EU Parliamentary elections of June 2004. Further delays beyond 2004 are, however, certainly possible, as enlargement has effectively become contingent on the success of internal reforms in the EU. Inadequate reforms of European institutions may also pose obstacles to successful EU candidates that wish to join European Monetary Union (EMU) at an early date. The body making monetary policy in the European Central Bank (ECB) is the Governing Council. It currently has 18 members - six Executive Board members and 12 national central bank governors, one for each of the 12 EMU member countries. Formally, all 18 members have equal weight in the decision making process. Eighteen members are already too many from the point of view of effective discussion, deliberation and collective decision-making. Enlarging an unreformed European Central Bank (ECB) to include ten new members would turn the current 18 member ECB Governing Council into an unwieldy, indeed unmanageable group (2).
Keywords: 330; Wechselkurspolitik; Wechselkurssystem; EU-Erweiterung; EU-Staaten; Osteuropa; Balassa-Samuelson Effekt; EU-Beitrittskriterien